Factors associated with motivation to volunteer among lecturers in Faculty of Medicine and Health Sciences, Universiti Putra Malaysia - Kamarudin, Muhammad Khairul; Wong, Nicholas Yew Jun; Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Shamsuddin, Nurainul Hana (Consortium of Islamic Medical Colleges, 2020)
Introduction: Volunteerism is an act that should be encouraged especially among the medical and health sciences community. In this study the motivation to volunteer among lecturers and its associated factors were assessed. Materials and Methods: This is a cross-sectional questionnaire study involving 91 lecturers who fulfilled the inclusion and exclusion criteria in the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia (FMHS, UPM) between May and July 2018. The Voluntary Function Inventory (VFI) was used to evaluate the motivations to volunteer. It consists of six subscales; values, understanding, social, career, protective, enhancement. Scoring is on a Likert scale of 1 to 7. Higher scores of each subscale indicates higher motivation. Results: The proportion of lecturers who do voluntary work is 85.7%. There were no significant association between the socio-demographic factors and volunteerism. The younger age group had a significant association with “career” subscale (median score = 4.6(IQR=1.8)) compared to the older age group (median score = 3.4(IQR=2.7)) (p=0.047). Female lecturers scored significantly higher for “protective” subscale (median score = 4.6(IQR=19)) compared to male lecturers (median score = 3.8 (IQR=2.6)) (p=0.021). Those who volunteered scored significantly higher for “values” subscale compared to those that didn’t volunteer, with a median scores of 5.9 (IQR= 0.8) and 5.4 (IQR 1.1) respectively, (p=0.027). There were no significant association between ethnicity and the income with other subscales. Conclusion: The motivations to volunteer for “career motive” were higher for the younger lecturers. Female lecturers scored higher for “protective motive.” Lecturers who were volunteers scored higher for “value motives” as compared to those who were non-volunteers.